The Detection of Retina Microvascular Density in Subclinical Aquaporin-4 Antibody Seropositive Neuromyelitis Optica Spectrum Disorders - Chen, Yihong; Shi, Ce; Zhou, Lili; Huang, Shenghai; Shen, Meixiao; He, Zhiyong (Frontiers in Neurology, 2020)
Keywords: Neuromyelitis optica spectrum disorders, Optical coherence tomography angiography, Diagnosis, Aquaporin-4 antibody, Optic neuritis.Purpose: To use optical coherence tomography (OCT) and OCT angiography (OCT-A) to measure changes in the retinal structure and microvasculature of patients with aquaporin-4 antibody-positive, neuromyelitis optica spectrum disorder (NMOSD) with a history of optic neuritis (NMOSD+ON) and those without it (NMOSD-ON). Methods: A total of 27 aquaporin-4 antibody-positive NMOSD patients and 31 age- and gender-matched healthy control (HC) participants were included. In 27 NMOSD patients, 19 of them had a history of optic neuritis (ON) and 8 of them had no history of ON. Peripapillary retinal nerve fiber layer (pRNFL) thickness and macular ganglion cell and inner plexiform layer (GCIPL) thickness were measured by OCT. Radial peripapillary capillary density (RPCD) and macular superficial vessel density (MSVD) were measured by OCT-A. Comparisons of retinal structural and microvascular parameters between the cohorts were performed using generalized estimating equation models. Diagnostic accuracy was evaluated by the area under the receiver operating characteristics curve (AROC). Results: In NMOSD+ON eyes, the GCIPL and pRNFL thicknesses, 48.6 ± 7.1 μm and 61.7 ± 25.1 μm respectively, were significantly thinner than in HC eyes (P < 0.001 for both). However, in NMOSD-ON eyes, the GCIPL and pRNFL thicknesses were not significantly thinner than in HC eyes (P > 0.05 for both). In NMOSD+ON eyes, the RPCD and MSVD, 37.8 ± 7.1% and 36.7 ± 5.0% respectively, were significantly less dense than HC eyes (P < 0.001 for both). Similarly, the RPCD and MSVD in NMOSD-ON eyes, 49.0 ± 2.8% and 43.9 ± 4.2% respectively, were also less dense than in HC eyes (P < 0.029 for RPCD, P < 0.023 for MSVD). The highest AROC, 0.845 (sensitivity = 88.5%, specificity = 78.0%), was achieved by the logistic regression combination of all of the variables, i.e., pRNFL, GCIPL, RPCD, MSVD. Conclusions: Retinal microvascular changes were present in NMOSD-ON eyes. The combination of retinal structural and microvascular parameters might be helpful to discriminate NMOSD-ON eyes from HC eyes.